Feasibility study of standalone PV-wind-diesel energy systems for coastal residential application in Pekan, Pahang - Roziah, Zailan; Siti Nurzalikha, Zaini; Muhammad Ikram, Mohd Rashid; A. A., Razak (EDP Sciences, 2017)
Techno economic study is feasible to optimize the usage of renewable energy components that targeting low cost of electricity generation system. The selected case study area is coastal area in Pekan, Pahang, Malaysia. The autonomous system designed in this study is hybrid standalone PV-wind-diesel energy system to fulfil a basic power demand of 20.1 kWh/day. Such power system was designed and optimized further to meet the power demand at a minimum cost of energy using energy optimization software, Hybrid Optimization Model for Electric Renewables (HOMER). The analysis focused on the operational characteristics and economics. The standalone PV-wind-diesel energy system has total net present cost about $61, 911 with cost of energy $0.66/kWh. Apparently, the generation of electricity from both wind turbine and PV can be inflated with the diesel generator. In comparison, return of investment (ROI) value turned out lower for Feed in Tariff (FIT) as compared to self-sustained house. Payback period also longer for FIT program that makes the selling back of electricity generated to Tenaga National Berhad (TNB) is considered not favourable.